Jerusalem, Israel/Palästina. Geophysikalische Erkundung der Lage und des Verlaufs der herodianischen Stadtmauer unter dem heutigen christlichen Viertel der Jerusalemer Altstadt - Vieweger, Dieter (e-Forschungsberichte des DAI, 2017)
The project aims to find traces of the Herodian city wall (‘Second Wall’) in Jerusalem. Since there is no possibility to undertake new excavations within the Old City the project uses geophysical methods. Within two seasons (autumn 2015 and 2016) the 7 m deep sondage underneath the Church of the Redeemer as well as several places at the Muristan, the Cardo, Suqs and of the ‘Via Dolorosa’ have been measured. The first season in 2015 was a pilot study in order to proof the geographical and local measurement conditions and to solve the technical challenges given by the deep and narrow sondage underneath the Church of the Redeemer as well as by a survey in an urban area. The geophysical survey of a historical city as Jerusalem pose some demands which requires new ground penetrating radar (GPR) concepts. The project tried to meet these requirements by the implementation of a unique GPR prototype. The new method has a large impact on the implementation technology of GPR devices leading to simplified electronics and better device performance. In the second season the locations mentioned above have been measured by using the new high sensitive devices.